Influence of Combined Supplemental Lighting and Nutrient Solution Concentration on Fruit Production and Quality of Cherry Tomato - Zhenbin Xie; Jinxiang Chen; Houcheng Liu; Riyuan Chen; Xiaolong Yang; Shiwei Song; Yiting Zhang (Horticulturae, 2024)
We conducted an analysis on the combined effects of two light conditions (L1: greenhouse natural lighting; L2: greenhouse natural lighting plus supplemental lighting (SL)) and three nutrient solution concentrations (EC, NS1: 3.2 dS/m; NS2: 3.7 dS/m; NS3: 4.2 dS/m) on the growth, fruit production, and quality of two cherry tomato cultivars with different fruit coloring (‘Baiyu’ and ‘Qianxi’). The plants subjected to NS2 exhibited enhanced growth, photosynthetic parameters, and fruit production. The utilization of SL further enhanced stem diameter, leaf number, and single fruit weight, resulting in higher fruit weight per plant in ‘Baiyu’, which was not observed in ‘Qianxi’. The growth, fruit size, and fruit weight of both cultivars cultivated under NS3 conditions were suppressed, while these fruits exhibited elevated levels of total soluble solids (TSS), soluble sugars, vitamin C, polyphenols, fructose, glucose, sucrose, citric acid, and carotenoids. These levels were further enhanced by SL treatment. The improvement of fruit quality through the application of SL was found to be cultivar and EC dependent. In ‘Baiyu’, SL at NS1 significantly enhanced the accumulation of fruit water, minerals (N, P, K, Ca, and Mg), TSS, vitamin C, fructose, sucrose, and carotenoids. However, this effect was not observed in ‘Qianxi’. The combination of SL and EC 4.2 dS/m (NS3) generally contributes to the enhancement of fruit quality, while SL and EC 3.7 dS/m can ensure consistent fruit production. The yellowish-white fruit cultivar exhibited higher levels of soluble sugars, vitamin C, and polyphenols under L2NS3 conditions compared to the red fruit cultivar, whereas the carotenoid content showed an opposite trend. The findings are anticipated to establish a theoretical foundation for the consistent annual cultivation of cherry tomatoes in protected horticultural settings.